Sistem Pendeteksi Alkohol Berbasis Sensor MQ-3 dan Internet of Things - Alviansyah Oktario Pratama; Ade Rohdiana; Rahma Rosaliana Saraswati (Jurnal DinamikA, 2020)
Today more and more food and beverages are mixed with some types of alcohol in disguise. Fatwa MUI No.4 Year 2003 states that " tidak boleh mengonsumsi dan menggunakan makanan/ minuman yang menimbulkan rasa/aroma (flavor) benda – benda atau binatang yang diharamkan". As per the current technological trend of Industrial Revolution 4.0. which focuses on internet-based technology using ESP8266 module so the researchers intend to make a detector of alcohol content that the results of its measurements can be known by real time by sending directly to the internet or known as Intenet of Things (IoT). This tool is expected to help the community, industry and government in determining the alcohol content of various products.Keywords : Alcohol, Sensor MQ-3, modul ESP8266